2001
DOI: 10.1046/j.1442-9071.2001.d01-21.x
|View full text |Cite
|
Sign up to set email alerts
|

Pterygium in Australia: a cost of illness study

Abstract: The direct medical costs of pterygium in Australia are AUD$8.3 m annually. This is likely to be an underestimate of total cost because indirect costs such as loss of work time could not be measured. More data are needed on the long-term benefits of pterygium intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 20 publications
(24 reference statements)
2
19
0
3
Order By: Relevance
“…Outro estudo do tipo populacional, realizado na Indonésia, país com características climáticas semelhantes ao Brasil, encontrou prevalência de 10% (10) , valor semelhante ao encontrado neste estudo. A influência da localização geográfica mais próxima da linha do equador, em que o clima quente favoreceria a ocorrência do pterígio, não é corroborada por estudos que observaram que na África (11) e na Austrália (12) a prevalência na população foi muito mais baixa, da ordem de 1,10%. Diante destes dados, a localização geográfica isoladamente não seria determinante para ocorrência de pterígio.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Outro estudo do tipo populacional, realizado na Indonésia, país com características climáticas semelhantes ao Brasil, encontrou prevalência de 10% (10) , valor semelhante ao encontrado neste estudo. A influência da localização geográfica mais próxima da linha do equador, em que o clima quente favoreceria a ocorrência do pterígio, não é corroborada por estudos que observaram que na África (11) e na Austrália (12) a prevalência na população foi muito mais baixa, da ordem de 1,10%. Diante destes dados, a localização geográfica isoladamente não seria determinante para ocorrência de pterígio.…”
Section: Discussionunclassified
“…Isto poderia ser decorrente de efeitos da radiação ultravioleta, devido à correlação existente entre esta condição e o desenvolvimento do pterígio (15)(16) , em que se observou que a radiação solar teria efeitos nocivos cumulativos, principalmente quando a exposição ocorre desde jovens e persiste por duas ou três décadas (15,17) . Com relação ao sexo, a ocorrência de pterígio foi maior entre os homens (10,4%), corroborando com a literatura (1,(12)(13) . Entretanto, estudos brasileiros mostraram acometimento de ambos os sexos, nas mesmas proporções (4) , ou predomínio no sexo feminino (18) .…”
Section: Discussionunclassified
“…Although previous studies report individuals from a higher ambient UVR region (Brisbane) spent less time outdoors compared to other regions of Australia including Tasmania, it must be noted that the intensity of UV exposure in Tasmania is lower [233]. The finding of higher CUVAF levels in Brisbane is consistent with previous work by Wlodarczyk et al who reported Queensland as having double the pterygium surgical rate per 100,000 when compared to Tasmania [234]. Thus, pterygium may well be a sensitive indicator of UV exposure, since the cornea focuses peripheral incident light approximately twenty fold onto the usual limbal location of pterygia [224].…”
Section: Discussionsupporting
confidence: 82%
“…In particular, the cornea and conjunctiva are exposed to higher levels of UV-B radiation and higher partial pressures of oxygen than most other tissues. The range of UV-associated eye diseases includes ocular surface squamous neoplasia, cataracts and pterygium, with pterygium having the highest incidence and highest associated health cost in Australia (Shoham et al 2008;Wlodarczyk et al 2001). Occasionally, ocular surface squamous neoplasia and invasive squamous cell carcinoma may develop on the basis of a pterygium.…”
Section: Introductionmentioning
confidence: 99%